Your best day: An interactive app to translate how time reallocations within a 24-hour day are associated with health measures - Dumuid, Dorothea; Olds, Timothy; Wake, Melissa; Lund Rasmussen, Charlotte; Pedišić, Željko; Hughes, Jim H; Foster, David Jr; Walmsley, Rosemary; Atkin, Andrew J; Straker, Leon; Fraysse, Francois; Smith, Ross T; et al. (PloS one, 2022)
Reallocations of time between daily activities such as sleep, sedentary behavior and physical activity are differentially associated with markers of physical, mental and social health. An individual's most desirable allocation of time may differ depending on which outcomes they value most, with these outcomes potentially competing with each other for reallocations. We aimed to develop an interactive app that translates how self-selected time reallocations are associated with multiple health measures. We used data from the Australian Child Health CheckPoint study (n = 1685, 48% female, 11-12 y), with time spent in daily activities derived from a validated 24-h recall instrument, %body fat from bioelectric impedance, psychosocial health from the Pediatric Quality of Life Inventory and academic performance (writing) from national standardized tests. We created a user-interface to the compositional isotemporal substitution model with interactive sliders that can be manipulated to self-select time reallocations between activities. The time-use composition was significantly associated with body fat percentage (F = 2.66, P < .001), psychosocial health (F = 4.02, P < .001), and academic performance (F = 2.76, P < .001). Dragging the sliders on the app shows how self-selected time reallocations are associated with the health measures. For example, reallocating 60 minutes from screen time to physical activity was associated with -0.8 [95% CI -1.0 to -0.5] %body fat, +1.9 [1.4 to 2.5] psychosocial score and +4.5 [1.8 to 7.2] academic performance. Our app allows the health associations of time reallocations to be compared against each other. Interactive interfaces provide flexibility in selecting which time reallocations to investigate, and may transform how research findings are disseminated.
Keywords: Humans; dítě; Austrálie; kvalita života; Sedentary Behavior; Quality of Life; Exercise; Mobile Applications; Child; Australia; mužské pohlaví; mobilní aplikace; Female; cvičení; sedavý životní styl; ženské pohlaví; Male; lidé